(untitled) (Medico Legal Update, 2019)
South Korea is experiencing increases in private health insurance (PHI). The purpose of this study is to examine the role of PHI on medical expenditure and unmet medical needs. This longitudinal study used data from the nationally representative 2011–2014 Korea Health Panel Survey (KHPS). Propensity score matching was performed to control the endogeneity from enrolling in PHI for the sake of healthcare utilization. Fixed-effects panel data analyses were performed to control for time-invariant factors. The final matched sample of 2,390 participants was retained throughout the study period. In this study, about 83.4% of the participants were covered by PHI in 2011 (fixed benefit 70.2%, indemnity 29.8%). Results from the fixed effects analysis with matched panel data showed that the impact of PHI on personal medical expenditure and unmet medical needs was not statistically significant. However, it was found that PHI had a positive and statistically significant influence on out-of-pocket (OOP) expenditure at point of use, including that for non-covered services. Particularly, indemnity type insurance plans had a large effect on OOP expenditure. The results show that PHI increased OOP expenditure but failed to decrease unmet medical needs. Additional analyses of the contribution of PHI and exploration of policy alternatives are required.